Surface roughness measuring in case of electro-erosion processed work pieces. (August 2019) - Popescu, D; Geonea, I
Abstract: Electroerosion is a manufacturing process for working difficult to machine materials. The paper describes a miniature punching die for perforation and cutting obtained from X15 using electro-erosion. This type of material cannot be processed using regular technologies because of its properties such as high hardness and complexity as well as protection against superficial layer damage. The manufacturing process provides a high quality and dimensional precision of the finished product. It is presented a digital surface roughness meter and the functional schematic of the PGI system. Also there are presented different roughness measurement variants as well as the graphical representation and the bearing area curve. There are emphasized the variations of the parameters in the 4 measurement points as well as the variation of the c coefficient. Finally the Ra, Rq and Rz parameters are analysed.